Measurement of neutrino oscillation parameters with the first six detection units of KM3NeT/ORCA - The KM3NeT collaboration; S. Aiello; A. Albert; A. R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; et al. (Journal of High Energy Physics)
Abstract KM3NeT/ORCA is a water Cherenkov neutrino detector under construction and anchored at the bottom of the Mediterranean Sea. The detector is designed to study oscillations of atmospheric neutrinos and determine the neutrino mass ordering. This paper focuses on an initial configuration of ORCA, referred to as ORCA6, which comprises six out of the foreseen 115 detection units of photo-sensors. A high-purity neutrino sample was extracted, corresponding to an exposure of 433 kton-years. The sample of 5828 neutrino candidates is analysed following a binned log-likelihood method in the reconstructed energy and cosine of the zenith angle. The atmospheric oscillation parameters are measured to be sin 2 θ 23 = 0.51 − 0.05 + 0.04 $$ {\sin}^2θ_{23}={0.51}_{-0.05}^{+0.04} $$ , and Δ m 31 2 = 2.18 − 0.35 + 0.25 × 10 − 3 eV 2 ∪ − 2.25 − 1.76 × 10 − 3 $$ Δ {m}_{31}^2={2.18}_{-0.35}^{+0.25}× {10}^{-3}{eV}^2\cup \left\{-2.25,-1.76\right\}× {10}^{-3} $$ eV2 at 68% CL. The inverted neutrino mass ordering hypothesis is disfavoured with a p-value of 0.25.